2015
DOI: 10.1371/journal.pone.0129632
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Mechanism for the Thermo-Sensitive Phenotype of CHO-MT58 Cell Line Harbouring a Mutant CTP:Phosphocholine Cytidylyltransferase

Abstract: Control and elimination of malaria still represents a major public health challenge. Emerging parasite resistance to current therapies urges development of antimalarials with novel mechanism of action. Phospholipid biosynthesis of the Plasmodium parasite has been validated as promising candidate antimalarial target. The most prevalent de novo pathway for synthesis of phosphatidylcholine is the Kennedy pathway. Its regulatory and often also rate limiting step is catalyzed by CTP:phosphocholine cytidylyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Since the catalytic domain is duplicated in Plasmodium CCT 22 , the Arg/His mutation was introduced at the respective positions of residue numbers 96 and 681 in the N-terminal and C-terminal halves of the protein, respectively. We have previously characterized this Arg/His point mutation within the second catalytic domain in vitro and demonstrated that the fold and the function of the protein is not damaged, whereas, thermal stability and dimer formation are heavily impaired 15 . To further prove that the rescue is linked to the enzymatic function of CCT, we engineered a Pf CCT variant harboring a mutation in the conserved HxGH motif, a unifying feature of the cytidylyltransferase superfamily which has been shown to function in substrate binding and catalysis 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the catalytic domain is duplicated in Plasmodium CCT 22 , the Arg/His mutation was introduced at the respective positions of residue numbers 96 and 681 in the N-terminal and C-terminal halves of the protein, respectively. We have previously characterized this Arg/His point mutation within the second catalytic domain in vitro and demonstrated that the fold and the function of the protein is not damaged, whereas, thermal stability and dimer formation are heavily impaired 15 . To further prove that the rescue is linked to the enzymatic function of CCT, we engineered a Pf CCT variant harboring a mutation in the conserved HxGH motif, a unifying feature of the cytidylyltransferase superfamily which has been shown to function in substrate binding and catalysis 28 .…”
Section: Resultsmentioning
confidence: 99%
“…CHO-MT58 is a Chinese Hamster Ovarian (CHO) cell line generated by chemical mutagenesis from CHO-K1 14 . In CHO-MT58, the cct gene contains a point mutation resulting in an amino acid change (R140H) that deteriorates catalytic domain dimer formation 15 . While at 37 °C (permissive temperature) functional protein is formed albeit in smaller amount, at 40 °C (non-permissive temperature) an accelerated rate of CCT degradation is observed as a result of the point mutation.…”
Section: Introductionmentioning
confidence: 99%
“…2, instead of the homodimer arrangement common to most CCTs [224]. The dimerization interface and tertiary structure are likely very similar to the homodimeric CCTs, as shown by recent modeling and MD simulations of the P. falciparum CCT [224,225]. The CCT catalytic domain is highly conserved, and the structure of the rat catalytic domain is a very good model for other CCT catalytic domains [224].…”
Section: Cct Structure and How It Explains Regulation By Membrane Binmentioning
confidence: 92%
“…Enzyme activity measurements were performed as described previously, using a continuous coupled colorimetric assay with pyrophosphatase (PPase), purine nucleoside phosphorylase (PNP) auxiliary enzymes and the auxiliary substrate 7-methyl-6-thioguanosine (MESG) 16 , 30 , 39 . For CTP substrate titrations, CTP concentration was varied between 100 μM and 2 mM while ChoP concentration was kept constant at 5 mM.…”
Section: Methodsmentioning
confidence: 99%